Chemoprotective role of quercetin in manganese-induced toxicity along the brain-pituitary-testicular axis in rats (2017)
Reproductive dysfunction in response to manganese exposure has been reported in humans and animals. Quercetin, a bioflavonoid widely distributed in fruits, vegetables and beverages has been shown to possess antioxidant, anti-inflammatory and anti-apoptotic activities in different experimental model systems. However, there is dearth of scientific information on the influence of quercetin on manganese-induced reproductive toxicity. This study was designed to evaluate the influence of quercetin on manganese-induced functional alterations along the brain–pituitary–testicular axis in rats. Manganese was administered alone at 15 mg/kg body weight or orally co-treated with quercetin at 10 and 20 mg/kg body weight for 45 consecutive days. Results indicated that quercetin significantly (p < 0.05) inhibited manganese-induced elevation in biomarkers of oxidative stress whereas it increased antioxidant enzymes activities and glutathione level in the brain, testes and epididymis of the treated rats. Furthermore, quercetin mediated suppression of inflammatory indices and caspase-3 activity was accompanied by preservation of histo-architectures of the brain, testes and epididymis in manganese-treated rats. The significant reversal of manganese-induced decreases in reproductive hormones (i.e. luteinizing hormone, follicle-stimulating hormone and testosterone) and testicular activities of acid phosphatase, alkaline phosphatase and lactate dehydrogenase by quercetin was complemented by an increase in sperm quality and quantity in the treated rats. Collectively, quercetin modulated manganese-induced toxicity along the brain–pituitary–testicular axis in rats via its intrinsic antioxidant, anti-inflammatory and anti-apoptotic activities, and may thus represent a potential pharmacological agent against manganese-induced male reproductive deficits in humans.